Development of Information and Communication Technology Learning Media - Muslim, Suyitno; Puspa Arum, Aniesa; Otto Fajarianto (JTP - Jurnal Teknologi Pendidikan, 2022)
This study aims to produce instructional videos on subjects that are feasible to be implemented as learning media for Postgraduate students and investigate the feasibility of learning videos at the UNJ location so that they are feasible to implement. as a learning medium. The development of learning videos for the State University of Jakarta uses a mix method approach using the Research & Development method by Allesi & Trollip, which consists of three development steps, namely planning: determining needs and goals, gathering resources, and generating ideas; design: making flowcharts and storyboards and drafting scripts; and development: producing video and audio, programming materials, preparing supporting components, evaluating, and revising. The results of development research are in the form of learning videos which are assessed by media experts, material experts, and students as media users. Overall the trial showed good results in the category according to the following details from material experts the average score of 5.55 was included in the appropriate category, from media experts the average score of 3.5 is included in the appropriate category, from small-scale trials involving students, an average score of 3.5 was obtained which was included in the appropriate category; and from large-scale trials involving students, an average score of 3.19 was obtained which was in the appropriate category. Based on the assessment of the feasibility of the media, it can be concluded that learning videos are suitable for use as learning media at UNJ.